The relationship between serum lipid levels and lifetime suicide attempts in patients with schizophrenia - Zeynep Baran Tatar (Medicine Science, 2018)
Patients with schizophrenia have a higher risk of suicide than the general population. Due to these high rates, researchers are investigating biomarkers associated with suicidal behavior to prevent suicide. Conflicting findings have also been reported in studies investigating the relationship between cholesterol and suicide in patients with schizophrenia. The aim of our study was to compare schizophrenia patients with and without a history of suicide attempt in terms of total cholesterol (TC), triglyceride (TG), high-density lipoprotein (HDL), and low-density lipoprotein (LDL) levels and to investigate the relationship between cholesterol levels and lifetime suicide attempts. A retrospective, cross-sectional study was carried out in a psychotic disorders outpatient clinic at a psychiatric hospital in Turkey. Two hundred and twenty-eight patients with schizophrenia were evaluated. We present a retrospective analysis of longitudinal data addressing socio-demographic characteristics, metabolic parameters, lipid profile, scales. Lifetime suicide attempts were reported by %28 of patients. It was found that schizophrenia patients with suicide attempt had higher TC and TG levels than schizophrenia patients without suicide attempt. Similar findings were repeated male patients with schizophrenia. In female patients, only TG level showed a significant difference between those with and without suicide attempt. Our findings indicate an association between high cholesterol levels and lifetime suicidality. The findings of our study may indicate that lifetime suicide attempt in schizophrenia exhibits a different lipid profile. [Med-Science 2018; 7(4.000): 826-30]